Analysis of Factors Affecting the Productivity of Self-Help Palm Oil Plantations in Mandiangin District Sarolangun - Ruth Alicia; Saidin Nainggolan (Politeknik Pertanian Negeri Samarinda, 2026)
This study aims to identify the characteristics of independent oil palm farmers, analyze the internal and external factors affecting their farming activities, and evaluate their effects on oil palm productivity, both directly and indirectly through the use of production inputs, in Mandiangin District, Sarolangun Regency. The study area was selected because it is one of the major smallholder oil palm production centers in the regency. Primary data were collected from independent oil palm farmers using structured questionnaires and analyzed using the Partial Least Squares (PLS) approach with SmartPLS and Microsoft Excel.The results show that independent oil palm plantations are still managed using conventional farming practices, while the use of production inputs has not fully complied with recommended standards, resulting in suboptimal plantation management. Farmers are generally of productive age, have primary to secondary education, moderate farming experience, and moderate levels of knowledge, motivation, and family dependency. External conditions indicate that marketing is still dominated by local collectors (toke), access to collection points is relatively easy, fertilizer availability is high, while fresh fruit bunch (FFB) prices remain relatively low. The structural model indicates that both internal and external factors have a positive and significant effect on oil palm productivity. Furthermore, internal factors have a positive and significant indirect effect through the moderating variable of production input use, whereas external factors have a positive but statistically insignificant indirect effect through the same variable.